AUTHENTIC ASSESSMENT IN PRACTICUM ACTIVITIES ON THE SCIENCE LECTURE (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This study aims to find out the application of authentic assessment in practicum activities on science lecture. This research is important because an authentic assessment can provide a comprehensive report about students' learning outcomes that include cognitive, affective and psychomotor skills. This is an expo-facto research. Sample in this study were students on science lecture at Primary School Teacher Education Departmen Faculty of Teacher Training and Education of Pasundan University Bandung. The instruments used student perception questionnaires, observation sheets, and interview guidelines. Data was analyzed by technique descriptive statistics. The results Showed that the authentic assessment in practicum activities has been applied Although not yet optimally. The student response of the authentic assessment on lectures showed positive results.